Revision of the Oriental Region genus Epicnemis Borgmeier (Diptera: Phoridae) - Brown, Brian V; Gonzalez, Lisa (Zootaxa, 2020)
The Oriental Region phorid genus Epicnemis Borgmeier is revised, resulting in the recognition of 15 species, 10 of which are new to science: E. alus, chaweewanae, digitalis, disjunctus, dorsalis, latus, projectus, ratanae, setosus, and sinuosus. Only males are treated, as females are highly modified and cannot be associated with their males based on morphology alone.